Correlation of serum Leptin and Vaspin contents with renal function, oxidative stress and inflammatory response in patients with diabetic nephropathy - Yun Ruan (Journal of Hainan Medical University, 2018)
Objective: To investigate the correlation of serum Leptin and Vaspin contents with renal function, oxidative stress and inflammatory response in patients with diabetic nephropathy (DN). Methods: A total of 109 patients with type 2 diabetes mellitus alone and 76 patients with diabetic nephropathy were selected as diabetes group and DN group, and 100 healthy volunteers who underwent physical examination in our hospital were selected as normal control group. The differences in serum Leptin and Vaspin contents as well as renal function index, oxidative stress index and inflammatory mediator levels were compared among the three groups, and the internal relationship of serum Leptin and Vaspin contents in DN patients with renal function injury, oxidative stress and inflammatory reaction were further analyzed. Results: Serum Leptin and Vaspin contents of diabetes group and DN group were higher than those of normal control group, and serum Leptin and Vaspin contents of DN group were higher. Peripheral blood renal function indexes serum creatinine (SCr), blood urea nitrogen (BUN), β2 microglobulin (β2-MG) and cystatin-C (Cys-C) levels of DN group were higher than those of diabetes group and normal control group; oxidative stress indexes reactive oxygen species (ROS) and reactive nitrogen species (RNS) contents were higher than those of diabetes group and normal control group whereas total antioxidant capacity (T-AOC) content was lower than that of diabetes group and normal control group; inflammatory mediators transforming growth factor-β (TGF-β), interleukin-1β (IL-1β), interleukin-18 (IL-18), monocyte chemoattractant protein-1 (MCP-1) and intercellular adhesion molecules-1 (ICAM-1) contents were higher than those of diabetes group and normal control group. Correlation analysis showed that serum Leptin and Vaspin contents in DN patients were positively correlated with the degree of renal function injury, oxidative stress and inflammatory response. Conclusion: Serum Leptin and Vaspin contents abnormally increase in patients with DN, and their specific contents can objectively reflect the degree of renal function injury and inflammation stress.